Sintering behavior of hydroxyapatite ceramics prepared by different routes - Chou Yong, Tan; Singh, Ramesh; Khai Liang, Aw; Wei Hong, Yeo; Sopyan, Iis; Wan Dung, Teng (2009)
The sintering behaviour of three different HA, i.e. a commercial HA(C) and synthesized HA by wet precipitation, HA(W) and mechanochemical method, HA(M) were investigated over the temperature range of 1000°C to 1350°C. In the present research, a wet chemical precipitation reaction was successfully employed to synthesize highly crystalline, high purity and single phase stoichiometric HA powder that is highly sinteractive particularly at low temperatures below 1100°C. It has been revealed that the sinterability and mechanical properties of the synthesized HA by this method was significantly higher than that of the commercial material and HA which was synthesized by mechanomical method. The optimum sintering temperature for the synthesized HA(W) was 1100°C with the following properties being recorded: 99.8% relative density, Vickers hardness of 7.04 GPa and fracture toughness of 1.22 MPam½. In contrast, the optimum sintering temperature for the commercial HA(C) and synthesized HA(M) was 1300°C with relative density of 98% and 95.5%, Vickers hardness of 5.47 GPa and 4.73 GPa, fracture toughness of 0.75 MPam½ and 0.82 MPam½ being measured, respectively.